Ethnic politics in Iran and it's Consequences on Kurdish identity - Ghaderzadeh, Assist.Prof. Dr. Omid (Sulaimani Journal for Humanities, 2025)
The discourse of ethnic politics in contemporary Iran has been a governmental discourse based on the Cultural engineering. The meaning created by this discourse was a unifying meaning with the aim of building a national identity that did not compromise with cultural diversity and plurality. Using the theoretical approach of critical discourse analysis, the ethnic politics of the governments after the Iran-Iraq war have been investigated. Based on the findings, two “post-political” and “antagonistic” visions can be identified in the ethnic politics of governments. The dominant vision on the ethnic politics of reformist and moderate governments has been post-political. In this point of view, by emphasizing unity and approximation and reconciliation between different and conflicting interests in the society as a precondition for building a nation, ethnic differences are not considered as original identities. The ethnic politics of fundamentalist governments has been of an antagonistic type and defines ethnic identities as otherness of Iranian-Islamic identity. In general, the ethnic politics of the governments can be summarized under the category of " Inclusive exclusion" and based on that, Kurdish identity is not accepted as an independent identity that has identity demands. The result of the ethnic politics has been the politicization of the Kurdish identity and its transformation into the resistance identity.
Keywords: Ethnic politics; Inclusive exclusion; Kurdish identity; IranianIslamic identity; Resistance identity